Latin American Economic Review (Springer, 2014)
An open-access general interest journal on topics relevant to Latin America, including theoretical and quantitative papers on economic, social and political-economy issues with a regional focus. Open-access sponsored by CIDE, the Centro de Investigación y Docencia Económicas.